2007
DOI: 10.1093/bja/aem168
|View full text |Cite
|
Sign up to set email alerts
|

Adding ketamine to morphine for patient-controlled analgesia after thoracic surgery: influence on morphine consumption, respiratory function, and nocturnal desaturation

Abstract: Adding small doses of ketamine to morphine in PCA devices decreases the morphine consumption and may improve respiratory disorders after thoracic surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
69
2
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(75 citation statements)
references
References 35 publications
3
69
2
1
Order By: Relevance
“…22 Of the 70 studies meeting inclusion criteria, 64 were suitable for inclusion in the quantitative analysis, and the remaining six were added to the qualitative analysis. These six studies reported data which were not useable in the quantitative analysis, such as median and range (two), mean only (one), mean and range (one), graphical data and SEM (one), and number of events of non-opioid rescue analgesia (one) were initially analyzed quantitatively, an additional 17 studies [70][71][72][73][74][75][76][77][78][79][80][81][82][83][84][85][86] were used to corroborate the results within the quantitative analysis, and the remaining six studies [87][88][89][90][91][92] were added to the qualitative analysis. All 70 studies had either low or unclear risks of bias in all six categories of the Cochrane Collaboration's tool for assessing risk of bias (see Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…22 Of the 70 studies meeting inclusion criteria, 64 were suitable for inclusion in the quantitative analysis, and the remaining six were added to the qualitative analysis. These six studies reported data which were not useable in the quantitative analysis, such as median and range (two), mean only (one), mean and range (one), graphical data and SEM (one), and number of events of non-opioid rescue analgesia (one) were initially analyzed quantitatively, an additional 17 studies [70][71][72][73][74][75][76][77][78][79][80][81][82][83][84][85][86] were used to corroborate the results within the quantitative analysis, and the remaining six studies [87][88][89][90][91][92] were added to the qualitative analysis. All 70 studies had either low or unclear risks of bias in all six categories of the Cochrane Collaboration's tool for assessing risk of bias (see Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…Supplementary 18,[20][21][22][25][26][27]29,30,32,34,36,40,41,44,45,50 cardiac or thoracic surgery (six trials), 19,23,35,37,38,53 orthopedic surgery (ten trials), 24,28,31,33,39,43,[47][48][49]51 and other surgery (three trials). 42,46,52 General anesthesia was used in 34 trials; one trial used PCA during and after a uterine artery embolization procedure, 29 and one used either general or regional anesthesia.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
“…A more recent study of 352 patients also showed a lack of benefit (Sveticic et al, 2008 Level II), but in another, the addition of ketamine to morphine PCA reduced pain scores and the incidence of nausea and vomiting, was opioid-sparing, and led to shorter duration of use of PCA compared with PCA morphine alone (Kollender et al, 2008 Level II). In patients after thoracotomy, although the addition of ketamine to PCA morphine did not improve pain relief it was opioid-sparing, and patients in the ketamine group spent less time with oxygen saturation levels <90% and had better forced expiratory volumes (Michelet et al, 2007 Level II).…”
Section: Ketaminementioning
confidence: 98%
“…In a study of postthoracotomy patients, the addition of ketamine to morphine for PCA was opioid-sparing but failed to improve analgesia; however patients in the ketamine group had better respiratory parameters (Michelet et al, 2007 Level II).…”
Section: Chaptermentioning
confidence: 99%